Mengakhiri Dualisme Ilmu: Analisis Kebijakan Pembelajaran di SMA Abdussalam dan MA Raudlatul Ulum Al-Kholiliyah Kubu Raya - Abdul Lutfy (Jurnal Pendidikan Indonesia, 2026)
The dichotomy between religious science and general science is still an epistemological problem in the education system in Indonesia which has an impact on the suboptimal integration of values and knowledge in the learning process. Although education policy has led to integration through the Independent Curriculum, practice in the field shows that there is a gap between policy and implementation, so that the integration of knowledge is still partial and not systematic. This research aims to analyze learning policies based on knowledge integration, examine its implementation in the learning process, and identify the challenges faced at Abdussalam High School and Raudlatul Ulum Al-Kholiliyah High School. This study uses a qualitative approach with a comparative case study, through data collection techniques in the form of interviews, observations, and documentation that are analyzed thematically-comparatively. The results of the study show that the two institutions have a commitment to the integration of knowledge, but with a different approach, where SMA Abdussalam emphasizes more on structured planning aspects, while MA Raudlatul Ulum is more oriented towards internalizing values in learning practices. However, implementation in both institutions still depends on the role of teachers and has not been supported by a standard pedagogical model and a standardized evaluation system. Epistemologically, the integration that has occurred is still at the instrumental level and has not changed the basic paradigm about the nature of science. These findings affirm the importance of strengthening more operational and transformative learning policies to realize systematic, sustainable, and meaningful integration of knowledge in education